Transition with heterogeneous labor - Katalin Balla; János Köllîo; András Simonovits (Institute for the Study of Labor (IZA), 2006)
We extend the benchmark model of Aghion and Blanchard (1994), assuming two segments of the emerging private sector that differ in workers' productivity. We look at the paths of employment, wages, taxes, labor costs and profits during and after the transition, up until the shock is fully absorbed. Viability is a function of the speed of job destruction and the strength of the initial shock to employment. In the long run, the system asymptotically converges to full employment. If the rate of job destruction is sufficiently low, the unemployment rates can get close to steady-state values during the transition. Within the realm of feasible scenarios, unemployment differentials are simultaneously determined by the speed of destruction, the level of benefits and the cross-subsidization of low-productivity groups. Lower benefits induce higher aggregate employment and inequalities throughout the redeployment process, while higher subsidies are conducive to lower inequalities and higher aggregate employment. The choice between low versus high benefits is a matter of preferences but the systems with subsidies dominate the systems with no subsidies. The subsidy has strongest marginal effect on employment and income when job destruction is fast and benefits are high.
Keywords: J64; P31; H53; 330; transition; heterogeneous labor; job creation; unemployment benefit; wage subsidy